Conspicuous production: Wine, capital and status. (October 2015) - Overton, John; Banks, Glenn
The recent expansion of the global wine industry, especially in developing countries, has brought to light the apparent phenomenon of conspicuous production. This form of economic activity is characterised by investment decisions that seek status and reputation alongside or, in many cases, ahead of profits. This paper examines the wine industry and uncovers examples of conspicuous production occurring at different scales, from celebrities and individual investors through to national strategies. Although the empirical evidence is somewhat scattered, we argue this is a source of capital of significance in the wine industry, and possibly in other sectors of the economy.